Il teatro greco e le basi logiche della persona - La Matina, Marcello (Scenari, 2025)
In this article, I would like to formulate a theory of the πρόσωπον by investigating the role Greek drama may have played in laying the foundations, not only conceptual and expressive, but above all logical, of the notion of the person. The Attic drama, flourished in classical Antiquity, took on the task of translating the content of traditional myths into a language suitable for representation. This task could only be accomplished by adapting the expressive resources of the available language: mimetic gestures. It was necessary to translate the mythical Doing of traditional heroes into an action that would show its structure, reasons and, at the same time, its genesis and life. The central role in this work was assumed by the πρόσωπον. The term, which had a long and varied fortune, indicated both the mask and the person of a myth, and those of the verb, but above all it indicated the persons involved in the enunciation. By virtue of this semantic polysemy, the πρόσωπον was able to operate the catalysis necessary for a content analysis of traditional tales and for the transformation of the diegetic-mythic Doing (which is always attributive, because it is linked to the Hero’s proper name) into a mimetic-dramatic Doing (on principle capable of stimulating a ‘polemical’ syntax). It is from the theatre and its ‘camouflage’ – and especially through the contribution of the philosophical and theological speculation of the Greek Fathers – that the path starts leading to the modern notion of person.